Schaum's Outline of Theory and Problems of Electronic Devices and Circuits / Schaum's Outline Series in Engineering - Cathley Jimmie J (Mcgraw Hill Book Company, 1989)
Circuit Analysis: Port Point of View, Semiconductor Diodes, Characteristics of Bipolar Junction Transistors, Characteristics of Field-Effect Transistors, Transistor Bias Considerations, Small-Signal Midfrequency BJT Amplifiers, Small-Signal Midfrequency FET Amplifiers, Frequency Effects in Amplifiers, Power Amplifiers, Operational Amplifiers, Feedback Amplifiers, Switching and Logic Circuits, Vacuum Tubes, Index.